1994
DOI: 10.1007/bf01426064
|View full text |Cite
|
Sign up to set email alerts
|

Spin polarization and cross sections of electrons elastically scattered from heavy alkaline-earth atoms

Abstract: Abstract. Semi-relativistic approach is employed to compute the differential and integrated cross sections, spin polarization P and the spin polarization parameters T and U for the scattering of electrons from barium and strontium atoms in the energy range from 2.0-300 eV. The projectile-target interaction is represented both by real and complex optical potential in the solution of Dirac equation for the scattered electrons. The real optical potential includes the static, a parameter free correlation polarizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
10
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 14 publications
5
10
0
Order By: Relevance
“…However, the present work with OPMD has a rough qualitative agreement with the work of Kelemen et al [20] at energies 1 and 2 eV, as observed from figures 1(a) and (b). It can be noticed from figure 1(e) that the OPMD calculations have also qualitative agreement with Kumar et al [16] for 10 eV incident energy. Furthermore, for 100 eV collision energy, OPMD and [16] produce similar cross sections both in trend and magnitude ( figure 3(c)).…”
Section: Dcs and Total Cross Sectionssupporting
confidence: 84%
See 3 more Smart Citations
“…However, the present work with OPMD has a rough qualitative agreement with the work of Kelemen et al [20] at energies 1 and 2 eV, as observed from figures 1(a) and (b). It can be noticed from figure 1(e) that the OPMD calculations have also qualitative agreement with Kumar et al [16] for 10 eV incident energy. Furthermore, for 100 eV collision energy, OPMD and [16] produce similar cross sections both in trend and magnitude ( figure 3(c)).…”
Section: Dcs and Total Cross Sectionssupporting
confidence: 84%
“…It can be noticed from figure 1(e) that the OPMD calculations have also qualitative agreement with Kumar et al [16] for 10 eV incident energy. Furthermore, for 100 eV collision energy, OPMD and [16] produce similar cross sections both in trend and magnitude ( figure 3(c)). As seen in the figure 1(f), the three predictions produce a good qualitative agreement with differences in the cross-section values, except for the low angles where a good agreement in trend and magnitude of DCS is noticeable.…”
Section: Dcs and Total Cross Sectionssupporting
confidence: 84%
See 2 more Smart Citations
“…Spin polarization of electrons elastically scattered from alkaline-earth-metal atoms was given by Dzuba et al. [3,6], Yuan and Zhang [5], and Kumar et al [8].…”
Section: Introductionmentioning
confidence: 99%